The role of third sector organisations in the management of social condominiums in Chile: the case of Proyecto Propio*. Issue 3 (3rd July 2019) - Vergara, Luz María; Gruis, Vincent; van der Flier, Kees
Abstract: In Chile, social condominiums are a significant part of housing for low-income households. After decades of occupancy, this housing stock shows signs of rapid deterioration and devaluation due to neglected maintenance. Given the weak governmental support in management practices, third sector organisations are positioning themselves as alternatives to providing technical solutions and contributing to the enhancement of opportunities and capacities among communities that live in deprived areas. However, little is known about the dynamics between these organisations and the communities they work with as well as their interactions with their institutional environment in the context of improving condominium management practices. Employing concepts of intermediation and institutionalisation, we analyse the practice of the organisation Proyecto Propio . We describe the dynamics of the intermediary role as implementer of housing policy and catalyst of social innovation, and the institutionalisation of these practices. The main characteristic of their intermediary role in condominium management practices is a holistic approach as implementer and catalyst for complex interventions, situating the users at the centre of the process. The main challenges are related to institutionalisation: the inclusion of more incentives to scale up and consolidate the third sector as a relevant actor in housing and condominium management.